Strategic IT governance and alignment in business settings - Haes, Steven de; Van Grembergen, Wim (Advances in business information systems and analytics, 2017)
This book investigates emergent research methodologies involving the application of information technology in organizations, focusing on best practices, implementation issues, and empirical research within the field.